Gabon : 2019 Article IV Consultation, Fourth and Fifth Reviews under the Extended Arrangement under the Extended Fund Facility, and Request for Waiver of Nonobservance of Performance Criteria, and Rephasing of the Remaining Purchases; Press Release; Staff Report; and Statement by the Executive Director. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper presents 2019 Article IV Consultation with Gabon and its Fourth and Fifth Reviews Under the Extended Fund Facility (EFF), and Request for Waiver for NonObservance of Performance Criteria, and Rephasing of the Remaining Purchases. Gabon's performance under the program supported by the IMF's EFF Arrangement has been broadly satisfactory. Macroeconomic conditions have continued to improve, with growth slowly picking-up, fiscal and external positions improving, and public debt declining. Going forward, bold and ambitious reforms are needed to generate higher, more inclusive, and resilient growth. Sustained implementation of structural reforms is critical. Efforts to close infrastructure gaps, improve human capital, deepen financial intermediation, clear domestic arrears, and enhance governance and anticorruption measures are necessary to improve the business climate and achieve higher and inclusive growth. Efforts should continue to further boost domestic revenue and contain nonpriority spending, while protecting investment and enhancing social protection. Improving public finance management and the efficiency of public investment is also important for growth prospects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet